JULY 2014 PLACEMENT ADS (The Accounting Review, 2014)
The deadline for free position ads to be included in this section of The Accounting Review is two months prior to the desired publication in the January, March, May, July, September, or November issues. Position ads, which are free with the purchase of a job posting in the AAA Career Center, should provide all relevant information about the available positions and must include contact information or application instructions for interested candidates. For more information on how to purchase a job posting in the Career Center, or for up-to-date, detailed information about the placement listings in this issue, please go to the AAA website at http://aaahq.org and click on “Career Center,” or call our office at 941-921-7747.SACRED HEART UNIVERSITY, John F. Welch College of Business anticipates one (1) full-time, tenure-track faculty opening in Accounting for Academic Year 2014–2015, pending budgetary approval. The position requires an academically qualified faculty member as defined by AACSB. Candidates with excellent teaching records, relevant business experience, and a demonstrated capability to produce scholarly work publishable in refereed journals are encouraged to apply. Rank is open and commensurate with experience. A “normal” teaching assignment includes evening courses. It is anticipated that the position may also require online teaching. The Welch College of Business is AACSB-accredited and offers degrees in Accounting, Business Administration, Business Economics, Finance, Marketing and Sport Management. The Welch M.B.A., in addition to being offered in Fairfield, is offered at our Luxembourg campus. Sacred Heart University is the second-largest Catholic university in New England. The Princeton Review includes SHU in its “Best 378 Colleges: 2014” and U.S. News & World Report ranks SHU among the best regional universities in the north in its America's Best Colleges publication, making it one of the top New England liberal arts colleges. Over 6,400 students are enrolled in its five colleges: College of Arts & Sciences; College of Health Professions; the NCATE-accredited Isabelle Farrington College of Education, University College, and the AACSB-accredited John F. Welch College of Business. Qualified candidates should submit a letter of interest, curriculum vitae, samples of publications or research papers, student evaluations, and three letters of reference to Dr. Barbara Tarasovich, Co-Chair of the Search Committee, Accounting and Information Systems Department, John F. Welch College of Business, Sacred Heart University, 5151 Park Avenue, Fairfield CT 06825. Materials may be emailed to: diviscontia@sacredheart.edu. Sacred Heart University is a comprehensive Catholic university and an AA/EOE employer.UNIVERSITY OF NOTRE DAME, Department of Accountancy invites applicants for a non-tenure-track faculty teaching appointment beginning Spring or Fall 2015. The successful candidate will be capable of teaching advanced financial reporting and auditing courses in the undergraduate and graduate programs. An ideal candidate will hold a Ph.D. in Accounting or have significant and relevant professional experience and possess a strong commitment to teaching. Please submit a cover letter, vita, three letters of recommendation, and evidence of teaching ability to acctdept@nd.edu. For more information about the University of Notre Dame, the Mendoza College of Business, and the Department of Accountancy please visit the department's website at: http://business.nd.edu/accountancy/. The University of Notre Dame is an Affirmative Action Employer with a strong commitment to fostering a culturally diverse atmosphere for faculty, staff, and students. Women, minorities, and those attracted to a university with a Catholic identity are especially encouraged to apply.THE UNIVERSITY OF TENNESSEE AT CHATTANOOGA, the AACSB-accredited College of Business, Department of Accounting invites applications for a full-time, tenure-track Assistant, Associate, or Full Professor position in tax/financial accounting to begin August 1, 2014. Candidates should hold a doctoral degree with an emphasis in accounting or expect to complete all degree requirements by his or her starting date. ABD candidates will be considered. A degree from an AACSB-accredited school is preferred as is a CPA. The ideal candidate will have teaching interests in taxation and financial accounting and have a research interest consistent with his or her teaching field with a possible intersection with other research areas. Candidates for Assistant Professor should demonstrate excellent teaching potential and have an academic background that strongly suggests an ability to establish an ongoing program of substantive research. Candidates for Associate or Full Professor should demonstrate excellent achievement in teaching and have a substantive research record that reflects a significant ongoing research program. Review of applications will begin immediately and will continue until the position is filled. The Chattanooga campus of The University of Tennessee is seeking candidates who have the ability to contribute in meaningful ways to the diversity and intercultural goals of the University. Please send cover letter, vita, and references, preferably by email to: facultyvitae15@utc.edu. The University of Tennessee Chattanooga is an EEO/AA/Title VI/Title IX/Section 504/ADA/ADEA. All qualified applicants will receive equal consideration for employment and will not be discriminated against on the basis of race, color, national origin, religion, sex, pregnancy, marital status, sexual orientation, gender identity, age, physical or mental disability, or protected veteran status.AUBURN UNIVERSITY, Raymond J. Harbert College of Business School of Accountancy is seeking to fill one full-time tenure-track Assistant Professor position, contingent upon final budget approval, beginning Fall 2014. Successful applicants must possess a Doctorate in Accounting, preferably from an AACSB-accredited institution, prior to the date of employment. The successful candidate must meet eligibility requirements to work in the U.S. at the time the time the appointment is scheduled to begin and continue working legally for the proposed term of employment. Excellent communication skills are required. While all areas of teaching and research will be considered, the areas of immediate need are AIS and financial. Candidates must have strong research credentials/potential and will be expected to publish in top-tier scholarly journals. The faculty member is expected to contribute in instruction, research, and service/outreach/extension. Candidates with professional certification are desired. Review of applications will begin April 15, 2014 and continue until a qualified candidate is recommended for appointment. To be considered, qualified candidates must submit a letter of application, curriculum vita/resume, teaching evaluations, a current working paper or dissertation proposal, a copy of all relevant transcripts, and contact information for three references. All application materials should be submitted to: http://aufacultypositions.peopleadmin.com/postings/445. Auburn University is an Affirmative Action/Equal Opportunity Employer. Women and minorities are encouraged to apply.UNIVERSITY OF NEVADA, RENO, Department of Accounting and Information Systems invites applications for two tenure-track appointments at the Assistant Professor level beginning July 1, 2015. Candidates must have an earned doctorate in accounting from an AACSB-accredited university by the time they commence employment. All teaching areas are welcome. Instructional excellence and quality publications in peer-reviewed journals are expected. Work experience and professional certification are preferred. The faculty member can expect to teach both undergraduate and graduate level accounting courses. Applications should include a cover letter, curriculum vitae, and the names and contact information for at least three references. Application materials must be submitted electronically on the UNR Human Resource website found at: https://www.unrsearch.com/postings/14559. Contact person: Sonja Pippin, search chair; Email: sonjap@unr.edu; Phone: 775-784-1337. Members of the search committee will be attending the AAA Annual Meeting in Atlanta, GA and the Western AAA Meeting in Salt Lake City, UT. All interested candidates attending these meetings are encouraged to schedule a meeting to learn more about our accounting positions at the University of Nevada, Reno. EEO/AA; women and under-represented groups are encouraged to apply.WESTERN MICHIGAN UNIVERSITY, Haworth College of Business, Department of Accountancy invites applications for a tenure-track position at the Assistant or Associate Professor level in any area of accounting beginning Fall 2015. Candidates must have a Ph.D. with an accounting major (or ABD with completion by end of 2015) from an AACSB-accredited school. Salary is competitive. Teaching responsibilities will be at both the undergraduate and graduate levels. The Department of Accountancy's primary emphasis is on instruction followed by a strong emphasis on intellectual contributions. We encourage faculty to engage in applied research, instructional development, and basic research, in that order. Service that advances the mission of the department is also important. Western Michigan University enrolls approximately 24,000 students. The University comprises six degree-granting colleges, a Graduate College, and an Honors College. The Haworth College of Business enrolls about 4,000 students. Approximately 160 accounting majors graduate each year. The Carnegie Foundation for the Advancement of Teaching has placed WMU among the 76 public institutions in the nation designated as research universities with high research activity. The Haworth College of Business and the Department of Accountancy are accredited by the AACSB at both the undergraduate and graduate levels. Direct applications and inquiries to: Dr. Donald Gribbin, Chair, Department of Accountancy, Haworth College of Business, Western Michigan University, Kalamazoo, Michigan 49008-5402; Email: donald.gribbin@wmich.edu. All applications must be submitted online at: http://www.wmich.edu/hr/jobs/index.html. Western Michigan University is an Affirmative Action/Equal Opportunity Employer, consistent with applicable Federal and State laws. All qualified applicants are encouraged to apply.UNIVERSITY OF REDLANDS, College of Arts and Sciences, Department of Business Administration and Accounting seeks a Director to lead our highly regarded, fast-growing accounting program. For more information, and instructions on how to submit application materials, please visit: http://www.redlands.edu/offices-directories/human-resources/17589.aspxNORTH CENTRAL MICHIGAN COLLEGE invites applications for Dean of Finance and Facilities, full-time. Salary/wage range: 73,614–95,685. The Dean of Finance and Facilities will serve as the Chief Financial Officer for the College. The Dean is responsible for a comprehensive program of business management including accounting, purchasing, inventory, budgeting, financial reporting and auditing, maintenance of buildings and grounds, plant, auxiliary business operations, support staff personnel, civil rights, insurance and risk management, and any other assigned responsibilities. A Bachelor's degree in an appropriate field (Accounting, Finance, Business Administration) from an accredited institution required; Master's Degree preferred. Certified Public Accountant preferred. At least three years of full-time administrative management experience; preferably in higher education. Strong interpersonal skills and technical skills. A complete job description and employment application are available at: http://www.ncmich.edu. Submit cover letter, resume, completed application for employment, three professional references, and copy of academic transcripts to: North Central Michigan College, Human Resources, 1515 Howard St., Petoskey, MI 49770; or Email dsouza@ncmich.edu. Review of applications begins on May 9, 2014.THE UNIVERSITY OF ALABAMA AT HUNTSVILLE, Department of Accounting, Economics, and Finance is seeking an intellectually curious Accountant to join our faculty. This tenure-track appointment starts in the Fall term of 2015. Candidates must hold a Ph.D. in Accounting or related field from an AACSB-accredited school or be ABD (having officially defended their proposal). Willingness to interact with local accounting professionals is a plus. We will consider candidates with research and teaching interests in all areas, but our specific instructional needs are in financial accounting. AACSB-competitive salary. UAH offers the best of both worlds: an intellectually active and well-published faculty and bright, motivated students to teach (our in-coming freshmen have the highest ACT scores in the state). We offer an extremely collegial faculty who regularly publish and socialize together. Cross-disciplinary research is common as intellectual curiosity knows no bounds. The College also offers Master's degrees in business, accounting, and information technology. Interested and interesting candidates should contact: Allen Wilhite, Chair, Department of Accounting, Economics, and Finance, The University of Alabama in Huntsville, Huntsville, AL 35899; Email: acc@uah.edu . Please include a vita and at least three references with your letter of application. Please refer to log number 15/16-131. UAH is an Affirmative Action/Equal Opportunity institution. We encourage applications from women and minority candidates.MISSISSIPPI STATE UNIVERSITY, College of Business seeks applications and nominations for the position of Professor, Adkerson Endowed Chair, and Director of the Richard C. Adkerson School of Accountancy. Candidates must have an earned Doctorate in an appropriate field and an established, sustained record of teaching, research, and service qualifying for appointment to the rank of Professor with tenure. Preferred qualifications include prior administration, and leadership experience; a record of fundraising and development, ability to articulate goals and implement strategies; and excellent communication skills. Candidates should submit a cover letter, curriculum vitae, contact information for three professional references, and a personal data information form online at: http://www.jobs.msstate.edu (PARF# 7937). Review of applications will begin immediately and continue until the position has been filled. Confidential inquires and nominations should be directed to: Michael J. Highfield, Search Committee Chair, at: m.highfield@msstate.edu. Mississippi State University is an Affirmative Action/Equal Opportunity Employer.UNIVERSITY OF PENNSYLVANIA, Wharton School, Accounting Department is seeking applicants for a full-time, tenure-track faculty position at any level, Assistant, Associate, or Full Professor, in Financial, Managerial, and Tax Accounting. Demonstrated ability or potential for high-quality research and teaching are important. Applicants must have a Ph.D. (expected completion by June 30, 2016 is acceptable) from an accredited institution and have an outstanding research record or potential. The appointment is expected to begin July 1, 2015. Applications, including cover letter, curriculum vitae, and recent publications or working papers, must be submitted via our secure website: https://accounting.wharton.upenn.edu/recruiting/. Junior-level candidates should also include contact information for up to three references who will be asked to submit letters of recommendation. The deadline for applications is November 24, 2014. Contact: Professor Brian Bushee, Accounting Department, The Wharton School, University of Pennsylvania, 1300 Steinberg-Dietrich Hall, Philadelphia, PA 19104-6365. The University of Pennsylvania is an Affirmative Action/Equal Opportunity Employer. All qualified applicants will receive consideration for employment and will not be discriminated against on the basis of race, color, religion, sex, sexual orientation, gender identity, creed, national or ethnic origin, citizenship status, age, disability, veteran status, or any other characteristic protected by law.ALBERTUS MAGNUS COLLEGE invites applications for a full-time faculty position to teach undergraduate and graduate courses in the Department of Business Administration, Management, and Sport Management beginning in the fall semester of 2014. The College is offering a Master of Science in Accounting program beginning Fall 2014. The candidate will be involved in the development of this program, as well as with the current undergraduate accounting programs. Candidates for this position will possess a doctorate in accounting. CPA certification is preferred. Experienced candidates should demonstrate an established teaching record and provide evidence of success in similar academic environments. For additional preferred qualifications, please refer to the online posting. Applicants are asked to submit electronically an application letter, curriculum vitae, statement of teaching philosophy, and list of references to: Dr. Nancy Fallon, Chair, Search Committee (nfallon@albertus.edu). Screening of candidates will begin immediately and will continue until the position is filled.CLAREMONT McKENNA COLLEGE (CMC), Robert Day School (RDS) of Economics and Finance invites applications for an Assistant or Associate tenure-track position in Accounting beginning Fall 2015, subject to budgetary approval. We seek an individual holding a Ph.D. in Accounting, with a commitment to excellence in teaching, research, and professional service. We offer competitive compensation and teaching responsibilities that enable a notable level of high impact research. Rank and salary are dependent on qualifications. Applications will be reviewed immediately. Position remains open until filled. Submit confidential cover letter, resume, teaching evaluations, three reference letters, and publications/working papers at: https://webapps.cmc.edu/jobs/. CMC is an elite liberal arts college 35 miles east of Los Angeles. CMC offers undergraduate degrees in Economics, Accounting, and a Master's degree in Finance. The College is part of the Claremont University Consortium. For additional information on The Robert Day School go to: http://www.cmc.edu/rdschool/. CMC is an Equal Opportunity Employer.BERRY COLLEGE, Campbell School of Business seeks to fill a tenure-track faculty position in Accounting beginning August 2015. Candidates should have an earned Doctorate in Accounting, be an excellent teacher, and have an established research agenda with refereed publications. Teaching responsibilities are primarily undergraduate auditing, AIS, and introductory accounting. Service responsibilities include undergraduate advising. Rank and salary will be commensurate with credentials and experience. Berry College is a comprehensive liberal arts college in northwest Georgia. The school is fully accredited by AACSB. Applicants should send a letter of application, current vita, evidence of current teaching effectiveness and scholarship, and three letters of recommendation to: Accounting Search, Office of the Dean, Campbell School of Business, Berry College, PO Box 495024, Mount Berry, GA 30149-5024. Screening begins August 2014, and will continue until the position is filled. Berry College is an Equal Opportunity Employer.